1995
DOI: 10.1002/pola.1995.080330822
|View full text |Cite
|
Sign up to set email alerts
|

Miniemulsion polymerization of styrene: Evolution of the particle size distribution

Abstract: The mechanism of the miniemulsion polymerization of styrene was investiaged through a combination of calorimetry to monitor the polymerization rate and transmission electron microscopy (TEM) to follow the evolution of the particle size distribution. These techniques proved to be a powerful combination for gaining detailed mechanistic information regarding these polymerizations. Particle size analysis of the latexes withdrawn during the course of the reaction revealed that most of the polymer particles were for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
72
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 21 publications
6
72
0
Order By: Relevance
“…It can be seen that the particle-size distribution is broader at the beginning of the polymerization and becomes narrower as the polymerization proceeds. At the end of the polymerization, monodisperse polymer particles were obtained, while Miller et al 29 reported from the miniemulsion polymerization of St that the particle-size distribution is narrower at the beginning of the polymerizations and generally becomes broader as the polymerization proceeds.…”
Section: Particle Size and Its Distribution During Polymerizationmentioning
confidence: 97%
See 1 more Smart Citation
“…It can be seen that the particle-size distribution is broader at the beginning of the polymerization and becomes narrower as the polymerization proceeds. At the end of the polymerization, monodisperse polymer particles were obtained, while Miller et al 29 reported from the miniemulsion polymerization of St that the particle-size distribution is narrower at the beginning of the polymerizations and generally becomes broader as the polymerization proceeds.…”
Section: Particle Size and Its Distribution During Polymerizationmentioning
confidence: 97%
“…Miller et al 29 studied in detail the evolution of the number of particles as a function of the fractional conversion for the different initiator concentrations studied. Their results suggested that the conversion at which nucleation ceases is determined to be between 40 and 60% conversion.…”
Section: Particle Size and Its Distribution During Polymerizationmentioning
confidence: 99%
“…36 The data in Table I, however, differ from those reported for the electrosterically stabilized emulsion polymerization of styrene where the desorption of radicals was depressed. [8][9][10] The decreased desorption of radicals was attributed to the thick emulsifier layer formed by the graft copolymer at the polymer particle surface. This difference between the present data and the literature ones might result from the difference in the solubility, the molecular weight and mobility of the stabilizers used.…”
Section: 37mentioning
confidence: 99%
“…This may not be a case for the high molecular weight copolymer. [8][9][10] The reduction in the polymerization rate with increasing the weight ratio of emulsifier and monomer can arise from the breakdown in the extent of compartmentalization of the free radicals in the latex particles and the increased exit of radicals. The decreased extent of compartmentalization of radicals is accompanied with the shapes of the conversion and polymerization rate curves (Figures 1 and 2) typical for the microemulsion polymerization characterized by the strong radical desorption.…”
Section: 37mentioning
confidence: 99%
See 1 more Smart Citation